The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1152/ajpgi.90489.2008
|View full text |Cite
|
Sign up to set email alerts
|

Apical targeting and Golgi retention signals reside within a 9-amino acid sequence in the copper-ATPase, ATP7B

Abstract: ATP7B is a copper-transporting P-type ATPase present predominantly in liver. In basal copper, hepatic ATP7B is in a post-trans-Golgi network (TGN) compartment where it loads cytoplasmic Cu(I) onto newly synthesized ceruloplasmin. When copper levels rise, the protein redistributes via unique vesicles to the apical periphery where it exports intracellular Cu(I) into bile. We want to understand the mechanisms regulating the copper-sensitive trafficking of ATP7B. Earlier, our laboratory reported the presence of ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
104
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(105 citation statements)
references
References 46 publications
1
104
0
Order By: Relevance
“…evaluate the activity, stability, and trafficking of ATP7B and its mutants (11,12). In this study, we combined these assays with additional mutational analysis and computational studies to dissect the molecular phenotype of WD mutations found in a highly conserved region of ATP7B, G 621 -S 668 .…”
Section: Significancementioning
confidence: 99%
“…evaluate the activity, stability, and trafficking of ATP7B and its mutants (11,12). In this study, we combined these assays with additional mutational analysis and computational studies to dissect the molecular phenotype of WD mutations found in a highly conserved region of ATP7B, G 621 -S 668 .…”
Section: Significancementioning
confidence: 99%
“…To evaluate the transport activity of ATP7B-Arg 875 , we used Menkes fibroblasts transfected with tyrosinase (YSTT cells). These cells lack endogenous copper-ATPase and are unable to transport copper into the TGN, thus producing inactive tyrosinase (9,10). The expression of ATP7B-Gly 875 in YSTT cells restores copper delivery to the TGN and activates tyrosinase, as evident from the formation of black pigment [levo-3,4-dihydroxy-L-phenylalanine (L-DOPA) quinone].…”
Section: Atp7b-arg 875 Does Not Show Transport Activity Under Basalmentioning
confidence: 99%
“…YSTT cells were maintained in DMEM with 10% (vol/vol) FBS, 200 μg/mL G418, and 0.5 μg/mL puromycin. The pcTYR plasmid was described earlier (10). For localization studies, the N-terminal FLAG tag was added to ATP7B by PCR and the construct was cloned into the pcDNA5 FRT/TO plasmid (Invitrogen).…”
mentioning
confidence: 99%
“…The apical transporters studied to date appear to have unique and complex sorting signals, the recognition systems are only beginning to be identified, and the targeting mechanisms are still largely unknown. More study is needed, particularly of patient missense mutations whose protein phenotypes (in hepatic cells) may give important clues about these processes (eg, see Braiterman et al 5 ). Second, are several apical PM protein recognition systems missing from hepatocytes?…”
Section: Hepatocellular Polarity: Its Establishment and Maintenancementioning
confidence: 99%